Topical application of ketamine to prevent postoperative sore throat in adults: A systematic review and meta‐analysis. Issue 5 (11th February 2020) - Kuriyama, Akira; Nakanishi, Misuzu; Kamei, Jun; Sun, Rao; Ninomiya, Kohei; Hino, Masaaki
Abstract : Background: Postoperative sore throat is a leading undesirable postoperative outcome. Ketamine is an N‐methyl‐d‐aspartate receptor antagonist and its topical application is used for chronic pain and oral/throat indications. We conducted a systematic review to assess the efficacy of preoperative, topical ketamine application for preventing postoperative sore throat. Methods: We searched MEDLINE, EMBASE, and CENTRAL through September 23, 2019 for randomized controlled trials in which at least one intervention was topical ketamine to prevent postoperative sore throat in adults undergoing endotracheal intubation. The primary outcome was the incidence of sore throat at 24 hours postoperatively. The comparators were non‐analgesic controls (placebo, no treatment, or usual care) or active agents. We pooled the data using a random‐effects model. Results: We included 41 randomized controlled trials involving 3784 participants. Topical ketamine was associated with reduced incidence of sore throat at 24 hours postoperatively compared to non‐analgesic methods (risk ratio, 0.45; 95% CI, 0.37‐0.54; P < .001). We found significant publication bias, but the results remained unchanged with a trim‐and‐fill analysis. Trial sequential analysis (TSA) suggested that the efficacy of topical ketamine was adequate (TSA‐adjusted 95% CI, 0.33‐0.56). The GRADE quality for this evidence was moderate. Topical ketamine was inferior to a combination of nebulized ketamine and clonidine in preventing postoperative sore throat. Conclusions: Preoperative, topical ketamine application may be more effective than non‐analgesic methods in preventing postoperative sore throat. The number of studies did not suffice to determine the place of topical ketamine among agents to prevent postoperative sore throat.